HOUSEMAN DEPARTEMENT HOUSEKEEPING GRAND MERANTI HOTEL KABUPATEN KEPULAUAN MERANTI - ", Supiyati; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The development of the hotel in the long run is very rapid and also become a very industry presents for the entrepreneurs who are in it. In the world of the hospitality industry, the quality of service becomes something very important karana customers always want to get the desired with the services provided by hotel employees to guests and customers hence required Standard Operations (SOP) is very good and required to always professional houseman departement housekeeping .In this study, researchers used the method of mix-method as a research procedure that produces data processing from interviews, documentation, observation, and questionnaires.The conclusion from the data processing shows that houseman departement housekeeping is categorized in good level, as seen from the result of 61% result from mean of calculation of questionnaire. And it can be concluded that, technically the employee's understanding and skill in using machine tools is good, houseman has a good conceptual in pursuing cleansing area, and division of duty done by supervisor is very fair.Keywords: houseman departement housekeeping, public area, machine tool